Home-based prehabilitation with exercise to improve postoperative recovery for older adults with frailty having cancer surgery: the PREHAB randomised clinical trial. (July 2022) - McIsaac, Daniel I.; Hladkowicz, Emily; Bryson, Gregory L.; Forster, Alan J.; Gagne, Sylvain; Huang, Allen; Lalu, Manoj; Lavallée, Luke T.; Moloo, Husein; Nantel, Julie; Power, Barbara; Scheede-Bergdahl, Celena; et al.
Abstract: Background: Frailty is a state of vulnerability as a result of decreased reserves. Prehabilitation may increase reserve and improve postoperative outcomes. Our objective was to determine if home-based prehabilitation improves postoperative functional recovery in older adults with frailty having cancer surgery. Methods: This double blind randomised trial enrolled people ≥60 yr having elective cancer surgery and ≥3 weeks from enrolment to surgery as eligible. Participation in a remotely supported, home-based exercise prehabilitation program plus nutritional guidance was compared with standard care plus written advice on age-appropriate activity and nutrition. The primary outcome was 6-min walk test (6MWT) distance at the first postoperative clinic visit. Secondary outcomes included physical performance, quality of life, disability, length of stay, non-home discharge, and 30-day readmission. Results: Of 543 patients assessed, 254 were eligible and 204 (80%) were randomised (102 per arm); 182 (94 intervention and 88 control) had surgery and were analysed. Mean age was 74 yr and 57% were female. Mean duration of participation was 5 weeks, mean adherence was 61% (range 0%–100%). We found no significant difference in 6MWT at follow-up (+14 m, 95% confidence interval −26–55 m, P =0.486), or for secondary outcomes. Analyses using a prespecified adherence definition of ≥80% supported improvements in 6MWT distance, complication count, and disability. Conclusions: A home-based prehabilitation program did not significantly improve postoperative recovery or other outcomes in older adults with frailty having cancer surgery. Program adherence may be a key mediator of prehabilitation efficacy. Clinical trial registration: NCT 02934230 .